Upcoming Need of Geriatric Healthcare: An investigation in India - Ghosh, Dona; Jena, Lalatendu Kesari (The journal of contemporary issues in business and government, 2022)
Purpose: With the background of surging greying population India has emerging pressure on the healthcare system because aged people are more susceptible to health problems. Therefore, present study aims: firstly to explore how the health complains among the elders are distributed across the rural-urban sectors; and secondly, what is the nexus between socioeconomic status and health complains. Research Design: The study has analysed unit-level data for the elderly (60 years and above).The analysis has two parts: firstly, the study explored the distribution of health complains using the descriptive statistics and econometric analysis explored the relationship between socioeconomic status and health complains across the sectors. Findings: The study finds that health situation of the elderly has deteriorated and the rural-urban sectorial gap has widened during over time. Findings suggest that socioeconomic status has close congruence with the self-reported health status but the relationship largely varies due to sectorial residency. Implications: Firstly, the study identified the trend of the elderly population’s perception of their health over a decade, which can help to understand the future healthcare demand. Secondly, the study conducted an in-depth analysis to comprehend how socioeconomic characteristics influence perceptions of health in a rural-urban framework, which can shed light on the sources of emerging healthcare needs. Originality: To the best of my knowledge, this is the first study to make an effort to pinpoint the sectorial geriatric health trajectory, the health gap, and related contributing socioeconomic determinants of the aged over a decade, specifically in the context of India.